2019
DOI: 10.2486/indhealth.2018-0168
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sleep quality of Thai intercity bus drivers

Abstract: This study aimed to describe sleep quality and explore factors associated with poor sleep quality in Thai intercity bus drivers. A cross-sectional design was employed with a sample of intercity bus drivers from 4 bus transportation companies. The Thai-PSQI was used to identify sleep quality, and the Thai Berlin Questionnaire used to assess sleep apnea risk. Data analysis included descriptive statistics and logistic regression. A total of 338 surveys were analyzed. All bus drivers were male; almost 66% of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…[25] A growing body of literature has evaluated the potential factors correlated with poor sleep quality among drivers, including fatigue, shift work, smoking, history of pulmonary disease, occupational stress, and driving times in a day. [23,[26][27][28][29]. In addition to forenamed factors, our analysis has also revealed a signi cant correlation between poor sleep quality and driving at night, which could be due to the interference of night shifts with circadian rhythm and following hormonal imbalances.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[25] A growing body of literature has evaluated the potential factors correlated with poor sleep quality among drivers, including fatigue, shift work, smoking, history of pulmonary disease, occupational stress, and driving times in a day. [23,[26][27][28][29]. In addition to forenamed factors, our analysis has also revealed a signi cant correlation between poor sleep quality and driving at night, which could be due to the interference of night shifts with circadian rhythm and following hormonal imbalances.…”
Section: Discussionmentioning
confidence: 92%
“…[22] Also, the same high prevalence of poor sleep quality has been reported in a similar study in the population of Thailand intercity bus drivers. [23] Reviewing seven sub-items of poor sleep quality, each of the components shows various rates of prevalence among drivers. In the literature, Sleep duration, in comparison to sleep quality, was better associated with accidents and accident risk [24].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to dangerous situations for the drivers themselves as well as for other drivers, with high mortality rates and damage to infrastructure (Lyznicki et al, 1998). Some studies have found that bus drivers experience poor sleep quality, which is of great concern for public safety and passengers alike (Chaiard et al, 2019;Diez et al, 2011;Sunwoo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bus drivers have self-reported that some of the main contributing factors to bus driver sleepiness are unrealistic scheduling, tight route schedules, turn-around and shift irregularity, and extended shift cycles (Biggs, Dingsdag & Stenson, 2006. Additionally, questionnaire data has revealed that sleepiness is a particular problem for those working night shifts or rotating shifts (Chaiard, Deeluea, Suksatit, & Songkham, 2019) and those working split shifts (Ihlström, Kecklund & Anund, 2017;Sando, Mtoi, & Moses, 2010).…”
Section: Introductionmentioning
confidence: 99%